PENGARUH CITRA MEREK DAN DESAIN TERHADAP KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE OPPO DI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS PAPUA - Elisabeth Awin Mayor; Louis S Bopeng; Yulius H Saptomo (Manis: Jurnal Manajemen dan Bisnis, 2020)
The purpose of this study was to determine the effect of Brand Image Variables on Purchasing Decisions, to determine the effect of Product Design Variables on Purchasing Decisions and to determine the effect of Brand Image Variables and Product Design on Purchasing Decisions on Smartphone Oppo Products. This research is an associative research with quantitative data and data sources include primary data and secondary data. The sampling method uses non probability sampling and the sampling technique uses purposive sampling. Data collection techniques using questionnaires, observation and literature study. Data analysis techniques in this study used multiple linear regression analysis, classic assumption test, R2, t test, F test. The results showed that the Brand Image Variable partially did not influence the Purchasing Decision and the Product Design Variable partially affected the Purchasing Decision. Simultaneous test results show that there is an influence of Brand Image Variables and Product Design on Purchasing Decisions. The company is expected to increase promotion about the quality of Oppo smartphone products.